2016
DOI: 10.4103/0301-4738.198856
|View full text |Cite
|
Sign up to set email alerts
|

Reduced-fluence photodynamic therapy and anti-vascular endothelial growth factor for polypoidal choroidal vasculopathy in an Indian population

Abstract: Aims:The aim was to study the efficacy of combined therapy with reduced-fluence photodynamic therapy (RFPDT) and intravitreal bevacizumab/ranibizumab from the Indian subcontinent.Settings and Design:This was a single-center, retrospective interventional study.Methods:Thirty-five eyes of 34 patients diagnosed with polypoidal choroidal vasculopathy were included. All the patients underwent RFPDT, followed by intravitreal bevacizumab/ranibizumab.Statistical Analysis Used:SPSS software, version 17.0 (SPSS Inc., Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Wong et al reported LogMAR VA improvement of 0.23 and polyp regression rate of 42.1% in the use of half-dose verteporfin PDT [17]. Other authors have reported the use of reduced dose rate for PDT resulting in LogMAR VA improvements ranging from 0.13-0.3, mean central foveal thickness decreases of 87-281 μm, and polyp regression rates between 71.4-92.8% [14,[16][17][18][19][20]. These results are comparable to those reported in our study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Wong et al reported LogMAR VA improvement of 0.23 and polyp regression rate of 42.1% in the use of half-dose verteporfin PDT [17]. Other authors have reported the use of reduced dose rate for PDT resulting in LogMAR VA improvements ranging from 0.13-0.3, mean central foveal thickness decreases of 87-281 μm, and polyp regression rates between 71.4-92.8% [14,[16][17][18][19][20]. These results are comparable to those reported in our study.…”
Section: Discussionmentioning
confidence: 99%
“…To mitigate the risk of complications using standard PDT, less intensive protocols for PDT treatment have been suggested. They include reducing the dose of verteporfin administered or reducing one of the laser parameters (dose rate or duration of laser application) to achieve a reduction in the laser fluence (light dose) [13][14][15][16][17][18][19][20]. Various authors have described treatment success with these less intensive protocols which theoretically reduces the risk of complications [13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sen et al . [ 24 ] showed that reduced-fluence PDT with anti-VEGF is safe and effective with polyp regression with visual improvement seen in 80% of cases. In their study, none of the patients developed subretinal hemorrhage.…”
Section: Discussionmentioning
confidence: 99%